Some Reflections on William Lane Craig's Critique of Islam - Ali, Zain (Heythrop journal, 2019)
William Lane Craig has recently formulated a set of arguments that aim to undermine the rationality of Islamic theism. This paper will consider seven arguments that Craig deploys against Muslim belief. The seven arguments can be summarised as follows: (1) the Quran makes an egregious historical error by denying the crucifixion of Jesus; (2) the Quran contains legendary stories about Jesus; (3) the Quran is mistaken about the self-understanding of Jesus; (4) the Quran misunderstands the Trinity; (5) the Islamic concept of God is morally deficient; (6) the Islamic concept of God is less plausible than a Trinitarian concept of God; and (7) the Muslim doctrine of salvation compromises God's holiness and proves to be unattainable. I contend that Craig's arguments, when examined closely, do not undermine the rationality of Islamic theism.